Obesity and bariatric surgery beliefs: Content analysis to design a scale - González, María Victoria (2021)
We describe the process by which items of a belief scale in obesity and bariatric surgery were generated using mixed methods. Participants were 22 Ecuadorian bariatric patients between 22 and 50 years old (M = 37.5, SD= 8.91). A semi-structured interview was constructed, validated, and conducted. The information was analyzed using directed content analysis, guided by the Health Belief Model. The beliefs varied according to sociodemographic and clinical characteristics, particularly age, sex, surgical technique, and postoperative evolution. The level of susceptibility, severity and benefits were mainly associated with the consequences of the loss of psychological well-being and social acceptance. Meanwhile, a greater perception of barriers was found in women, people who experienced negative emotions and those with less social support.